The Effect of Sappan Wood Extract (Caesalpinia sappan), Wheat grass and Vitamin E Treatment on the Liver Structure of Iron overload of Rat (Rattus norvegicus) - Safitri, Ratu; Reniarti, Lelani; Madihah, Madihah; Delia, Lila; Syamsunarno, Mas Rizky A.A; Panigoro, Ramdan (KnE Life Sciences, 2017)
This research was carried out to detect the effect of Sappan Wood Extract (Caesalpinia sappan), Wheat grass and Vitamin E Treatment on the liver structure of iron overload rat (Rattus norvegicus).The method of experimental used Completely Random Design (CRD in triple repetition. The treatment had been carried out orally. Iron dextran with total dose of 1.5 g kg-1 of body were given to rat on the first, fourth, seventh, ten and thirteenth day. Sappan Wood Extract (Caesalpinia sappan)200 mg kg-1 bw, 400 mg kg-1 bw, Wheat grass extract 100 mg kg-1 bw and Vitamin E 60 mg kg-1 bw were given to rat everyday for 15 days. At the seventeenth, rat were killed and their liver were taken. The observed parameters are morphological abnormality including the colour, the contour, ratio between liver weight and body weight as well as histological destruction. The result showed iron dextran treatment was proved the abnormality on morphological and histological desruction. Futhermore, Sappan Wood Extract (Caesalpinia sappan), Wheat grass and Vitamin E Treatment can decrease the morphological abnormality and the liver histological destructionon of iron overload rat. Keywords: Sappan Wood Extract, Wheat grass, Vitamin E, Iron, Morphological abnormality, Histological destruction